A Personal Perspective on the Methodological Practices of an Applied Fluvial Geomorphologist - Brierley, Gary (Espaço Aberto, 2016)
What is useful geomorphology? How do we do it (what methods do we use)? How can we help ensure that it is used, and it is used effectively? Here I share a few thoughts from the perspective of an applied fluvial geomorphologist. This is very much a personal, reflective contribution. Now at the ‘senior' end of professorial status (more than 10 years a full professor), I think it is interesting to reflect upon how methodological practices that I have used have changed during my career. In a sense, this is very much a record of my own journey, outlining decisions made along the way, and providing an account of some of the outcomes.